2013
DOI: 10.1016/j.ssc.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic tranmission through perforated plates with fractal subwavelength apertures

Abstract: ElsevierGómez Lozano, V.; Uris Martínez, A.; Candelas Valiente, P.; Belmar Ibáñez, F. (2013). Acoustic transmission through perforated plates with fractal subwavelength apertures. Solid State Communications. 165:11-14. ABSTRACTThe acoustic transmission response of plates perforated with fractal subwavelength holes array is studied. The Sierpinski Carpet pattern is used as fractal geometry.Ultrasound transmission spectra show that each iterative Sierpinski Carpet has the characteristic peaks and dips of the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The minimum is produced by a coherent interference. The Wood anomaly for normal incidence is given by 22 22 mn c p p , where  is the wavelength and n  N, that the resonant transmission peaks are directly related to the plate thickness, therefore when the plate thickness increases, more transmission maxima will appear and they will move toward lower frequencies. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum is produced by a coherent interference. The Wood anomaly for normal incidence is given by 22 22 mn c p p , where  is the wavelength and n  N, that the resonant transmission peaks are directly related to the plate thickness, therefore when the plate thickness increases, more transmission maxima will appear and they will move toward lower frequencies. …”
Section: Resultsmentioning
confidence: 99%
“…The role of the geometrical parameters of the hole array is important in the ultrasonic transmission through perforated plates and has been subject of several studies [18][19][20][21][22]. The purpose of this paper is to describe and summarize theoretically the set of geometrical parameters that affect the ultrasonic transmission through subwavelength holes arrays.…”
Section: Introductionmentioning
confidence: 99%
“…These structures are capable of producing sharp attenuation by means of destructive interference, as well as focalization through constructive interference. Gomez-Lozano et al [9] studied the transmission response in perforated plates with subwavelength holes. The transmission spectrums showed that every iteration with the Sierpinski carpet has the characteristic peaks and dips associated with the lattice constant of each matrix pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Castiñeira-Ibañez et al [7,8] presented an acoustic barrier for noise control formed by rigid cylinders arranged in fractal Sierpinski triangle geometry. Gomez-Lozano et al [9] studied the acoustic transmission response of perforated plates with a fractal subwavelength holes array. The ultrasound transmission spectra showed that each iterative Sierpinski Carpet has the characteristic peaks and dips of the lattice constant of each array that formed the pattern.…”
Section: Introductionmentioning
confidence: 99%